Investigating The Association Of Apolipoprotein E (Apoe) Gene Polymorphism And Its Associated Factors To Cardiovascular Disease (Cvd) In Type 2 Diabetes Mellitus (T2dm) Patients - Muzaidi, Nur Alya Syamimie (2022)
Apolipoprotein E (APOE) gene is widely acknowledged for its crucial function in the process of lipid metabolism and it is associated with elevated likelihood of cardiovascular disease (CVD) among Type 2 diabetes mellitus (T2DM) subjects. Controlling the risk factors may help lower the likelihood of developing this disease. The current study has analysed the associations between the APOE gene polymorphism and selected risk factors, as well as lipid profiles among patients diagnosed with a combination of T2DM and CVD. A total of 101 subjects aged between 18 and 80 years old were recruited in this study and were classified into two groups; 59 T2DM subjects with CVD and 42 subjects without CVD. APOE genotyping was done using the polymerase chain reaction-restriction fragment length polymorphism (PCR-FRLP). The ε3/ε3 genotype was the most common among both groups of T2DM patients with and without CVD, followed by ε2/ε4, ε3/ε4, ε2/ε3 and ε2/ε2 genotypes. However, the ε4/ε4 genotype was not present in either group. Multiple logistic regression (MLR) results revealed; that the ε3/ε3 genotype (0.052) (95% Cl 0.003, 0.792), ε3/ allele (34.830) (95% Cl 1.118, 1085.134), SBP (1.046) (95% Cl 1.002, 1.091) and HbA1c (2.286) (95% Cl 1.577, 3.314) were relevant and significant (p-value <0.05). In addition, the association between APOE gene polymorphism and lipid profile has demonstrated that the ε3/ε3 genotype was significant at low-density lipoprotein cholesterol (LDLC).